2006
DOI: 10.1523/jneurosci.4032-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor α But Not Interleukin 1β Mediates Neuroprotection in Response to Acute Nitric Oxide Excitotoxicity

Abstract: Neurodegenerative processes in the brain are accompanied by activation of innate immunity, which involves the release of proinflammatory cytokines by microglia and infiltrating macrophages. The beneficial or detrimental roles of these cytokines, including interleukin 1␤ (IL-1␤) and tumor necrosis factor ␣ (TNF-␣), remain to be clarified. These cytokines have numerous overlapping activities that make it difficult to interpret data generated by mice that have a mutation in the gene encoding either TNF-␣ or IL-1␤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(95 citation statements)
references
References 30 publications
3
89
0
1
Order By: Relevance
“…3 In this regard, microglia inhibition causes extensive damages in acute models of neurotoxicity, where TNF-a/IL-1b double knockouts have larger nitric oxide-induced neuronal damages compared to their wild-type counterparts. 94 Since microglial cells in these animals are unable to mount a proper innate immune response in this model of neurotoxicity, we propose that microglia are indeed beneficial to the prevention of neuronal death and the re-establishment of a functional neural environment. In addition, a few studies have demonstrated that an immune response in the CNS may be beneficial to the organism since it reduces the amount of amyloid deposition.…”
Section: Innate Immunity and Alzheimer's Diseasementioning
confidence: 89%
“…3 In this regard, microglia inhibition causes extensive damages in acute models of neurotoxicity, where TNF-a/IL-1b double knockouts have larger nitric oxide-induced neuronal damages compared to their wild-type counterparts. 94 Since microglial cells in these animals are unable to mount a proper innate immune response in this model of neurotoxicity, we propose that microglia are indeed beneficial to the prevention of neuronal death and the re-establishment of a functional neural environment. In addition, a few studies have demonstrated that an immune response in the CNS may be beneficial to the organism since it reduces the amount of amyloid deposition.…”
Section: Innate Immunity and Alzheimer's Diseasementioning
confidence: 89%
“…Pups aged 5-7 d (P5-7) were considered neonates (13,16,19,39). IL-1β −/− mice on a B6 background were the generous gift Scott Berceli (University of Florida, Gainesville, FL) and have been described previously (40). Mixed-sex litters were used for all neonatal studies.…”
Section: Methodsmentioning
confidence: 99%
“…C57BL/6 mice deficient in tumor necrosis factor (TNF) and/or interleukin-1␤ (IL-1␤), or expressing green fluorescent protein (GFP) under the control of the chicken ␤-actin promoter, were generated from breeders originally obtained from The Jackson Laboratory. Genotypes were confirmed by PCR as described previously (Turrin and Rivest, 2006). All experiments were performed on males aged 2-3 months in accordance with the guidelines of the Canadian Council on Animal Care.…”
Section: Methodsmentioning
confidence: 99%